2012
DOI: 10.1021/ma2026435
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Tracking of Microstructure Spacing and Ordered Domain Compression during the Drying of Solution-Cast Block Copolymer Films Using Small-Angle X-ray Scattering

Abstract: Changes in the spacing of hexagonally packed cylinders in a poly(styrene-b-butadiene) copolymer film during the continual extraction of toluene under different solvent removal conditions were studied by in situ small-angle X-ray scattering (SAXS) measurements. As the solvent is removed from the film, the structure spacing increases due to increasing segregation power and then decreases as the polymer chains become kinetically trapped while microdomains continue to deswell. The structure spacing in the vertical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 27 publications
2
11
0
Order By: Relevance
“…WAXS typically measures scattering from a q of approximately 10 -2 Å -1 to 10 1 Å -1 (nm to Å size scale analysis) [97][98][99]. Using in situ SAXS and WAXS during thermal annealing, BCP domain rearrangement has been studied on chemically-patterned substrates [100,101], during SVA [102], during electric field exposure [103,104], and upon drying after film casting [54,[105][106][107][108]. Notably, SAXS and WAXS examinations of BCP thin films are limited by the relatively small scattering volumes, the potential for radiation damage to the film, and inadvertent structural reorganization from sample interactions with X-rays [111][112][113].…”
Section: Transmission X-ray Scattering For In-plane Analysis Of Thin mentioning
confidence: 99%
See 1 more Smart Citation
“…WAXS typically measures scattering from a q of approximately 10 -2 Å -1 to 10 1 Å -1 (nm to Å size scale analysis) [97][98][99]. Using in situ SAXS and WAXS during thermal annealing, BCP domain rearrangement has been studied on chemically-patterned substrates [100,101], during SVA [102], during electric field exposure [103,104], and upon drying after film casting [54,[105][106][107][108]. Notably, SAXS and WAXS examinations of BCP thin films are limited by the relatively small scattering volumes, the potential for radiation damage to the film, and inadvertent structural reorganization from sample interactions with X-rays [111][112][113].…”
Section: Transmission X-ray Scattering For In-plane Analysis Of Thin mentioning
confidence: 99%
“…Additionally, the use of in situ characterization tools can help identify the underlying driving forces for nanostructure evolution, such as intermediate pathways to domain restructuring from as-cast to annealed states [42,[53][54][55]. Due to these advantages, in situ characterization of BCP thin films has provided key fundamental insights into various annealing approaches.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of morphology evolution in BCP and BCP-blend materials has been the subject of extensive research during the past 20 years, however, mostly with focus on the nucleation and growth process during the early state of microphase separation. Pioneering work on the characterization of GB defects by the Thomas and Hashimoto groups established the distinct types of GB structures in lamellar BCP microstructures: twist (helicoid and Scherk surface) and tilt (chevron, omega, and T-junction) boundary morphologies. Insight into the energetics of GB defects was first provided by numerical simulations that revealed the energy of GB defects to sensitively depend on the GB type as well as the misorientation between grains. , The results further suggested that the frequency of grain misorientations in quiescent organized BCP microstructures follows a Boltzmann distribution. Both predictions were experimentally validated by Ryu et al using triple-junction analysis .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Among all these morphologies, vertically oriented and hexagonally packed periodic channels permeating through the lms over large areas aer removal of the cylindrical domains have been extensively investigated because of their potential applications as nanoreactors, masks for depositions and patternings of functional components, precursors or templates for other nanostructured materials and size-selective separation. 1,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Thus, controlling the vertical orientation throughout the lms is the key to achieve such well-dened nanostructured materials, and to date, diverse approaches have been developed, including solvent and thermal annealing, [25][26][27][28][29][30][31][32][33][34][35][36] external application of electric, magnetic and shear elds, 23,[37][38][39][40][41][42] chemical modication of surfaces and/or topographical patternin...…”
mentioning
confidence: 99%
“…[43][44][45][46][47][48][49][50][51][52][53][54] Another key feature of such well-dened nano-porous materials is the domain sizes of vertically oriented channels that usually ranged between about 10 and 55 nm, and showed uncontrollable BCP system dependencies. 55 Even though the size of the cylinders or channels could be slightly tuned by the molecular weights and architectures of the BCPs and preparation conditions such as annealing temperatures and blending with compatible homo-polymers etc., 27,31,[56][57][58] controlling the size of cylinders or channels below 10 nm still remains challenging work. Rong-Ming Ho et al 30 reported preparation of poly(L-lactide) cylinders in polystyrene-b-poly(L-lactide) (PS-PLLA) thin lms with less than 100 nm thickness via solvent evaporation, and aer hydrolysis of PLLA, well-oriented nanochannel arrays over a large area with controlled domain sizes from 10 to 20 nm could be obtained.…”
mentioning
confidence: 99%